Cardiac rhabdomyomata in tuberous sclerosis: their course and diagnostic value. Issue 2 (February 1989) - Smith, H C; Watson, G H; Patel, R G; Super, M
Abstract : Echocardiography was performed in 60 people with tuberous sclerosis to ascertain the prevalence and course of cardiac rhabdomyomata at different ages. Twenty five (58%) of 43 children had tumours, but only three (18%) of 17 adults. The tumours tended to remain the same size through childhood. Only three infants were included but evidence from this and some published case reports suggest that the tumours tend to regress in early infancy and again in adolescence. The prevalence of tumours in young infants with tuberous sclerosis is likely to be considerably above 50%. As other signs of tuberous sclerosis are usually absent at this age echocardiography may afford the most useful diagnostic test in early infancy.